Isochronal recovery of electro-magnetic energy loss and electrical resistivity in yttrium-iron garnet ( Y3Fe5O12) - Abdullah, Nor Hapishah (2012)
Ferrites, including garnets are magnetic ceramics which have been used in the microwave and non-microwave frequency region for more than eight decades. Radio antenna, and high frequency transformers are just a few examples of devices in which ferrites are applied. The high electrical resistivity and excellent magnetic properties make ferrites a preferred choice in electronics and telecommunications in higher frequency region (upper MHz and GHz). One long standing research interest which covers both fundamental concerns and practical importance is a clear understanding of the origin or causes of electromagnetic (EM) energy loss in ferrites. This knowledge would greatly contribute towards producing very low-loss antenna and circuit-component ferrite materials. Hence yttrium-iron garnet (YIG) was chosen for the present research on account of its being the best low-loss applications. Since microstructural effects on EM energy loss are well understood, we propose instead to establish whether or not crystal atomic defects have any influence on such loss. For this intention, we have borrowed from metallurgists, a simple but powerful probing technique involving defects creation and their subsequent elimination within equal time-length durations: this is a technique for establishing isochronal recovery behaviour of any atomic defects-dependent properties. We chose to investigate experimentally the effect on a sample’s properties which are important to microwave scientists and engineers, after undergoing quenching and annealing treatments. In this study, YIG was prepared via mechanical alloying involving a 24 hours milling time of a mixture of yttrium oxide (Y2O3) and iron oxide (Fe2O3). The samples were then sintered at different temperatures between 900°C to 1350°C and optimized for microstructure. The samples were then heated for 2 hours at 1000°C and quenched in cooking oil. Then, annealing of the samples at 1000°C for 2 hours was carried out. The microstructure, magnetic and electrical properties before and after quenching also after annealing were studied in order to understand the physical, magnetic and electrical properties of the resulting materials. The X-Ray diffraction results confirmed the formation of the crystalline phase after sintering at 900°C. The microstructure studies of Y3Fe5O12 showed that the grain size increased and the pore size was estimated to be decreased as sintering temperature increased. The permeability and loss factor showed an isochronal recovery behaviour in which a parameter’s value was decreased after quenching and increased back even higher after annealing. This suggests that magnetic permeability and energy loss in YIG could significantly show an atomic defect-dependent behaviour. The resistivities of samples also could be observed to have an isochronal recovery behaviour in whichthe value dropped after quenching and increased almost gradually back even higher after an isochronal annealing series starting from 500°C to 1000°C. The values of resistivity were dropped after quenching due to defects created which are known as atomic vacancies and interstitials that might act as an electron donor which increased the value of the conductivity hence giving lower resistivity. Isochronal annealing on the other hand could be understood as a filling back of the vacancies slowly from low to high annealing temperature, yielding after the recovery on the values which is equal or higher than that of the as prepared sample. The corresponding results on the values of the permeability and the loss factor, strongly suggest that the decreases and increases in those values were associated with the creation and elimination, respectively, of atomic scale defects. The findings on the isochronal recovery behaviour of the permeability, energy loss and resistivity for these samples hopefully will help produced a better quality YIG with very low energy loss and very high resistivity to be used in electronic devices operating in the frequency range of 1 MHz to 1 GHz, as covered in this study.